Institutionalized adolescents and their relationship with drugs: an approach with socio-poetic inspiration - Leila Memória Paiva Moraes; Violante Augusta Batista Braga (Rev Rene)
We aimed at showing the feelings of a group of institutionalized adolescents and their relationship with drugs. We tried to favor the expression of the feelings related to drug abuse through creative mechanisms and identify the way they experience it. Fifteen adolescents of a Public Institution in Fortaleza – CE participated in the research. Data were collected through the group-researcher method, with inspiration in socio-poetry, working through exchange-of-experience workshops. It was possible to verify that the group had already been in touch with drugs, recognizing the relationship between drugs, violence and pleasure. Search for pleasure, escape from living conditions, amongst other things, were pointed as stimuli for the use, causing scars that last for a lifetime; the family’s absence, prejudice, lack of expectations are aspects that make them unhappy. We finished by building a collective construction with signs, footprints and shades of watercolor painted by several hands, where the colors sketch feelings and share pieces of experience.